To solve for the missing exponent in the equation \( s^{500}s^{?}=s^{175} \), we can use the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
-
Apply the property of exponents: \[ s^{500} s^{?} = s^{500 + ?} \]
-
Set the equation equal to \( s^{175} \): \[ s^{500 + ?} = s^{175} \]
-
Since the bases are the same, we can set the exponents equal to each other: \[ 500 + ? = 175 \]
-
To find the value of \( ? \), we subtract 500 from both sides: \[ ? = 175 - 500 \]
-
Calculate: \[ ? = -325 \]
Thus, the missing exponent is \(-325\).